MODELANDO LA POPREZA MULTIDIMENCIONAL UN ANALISIS ESTOCASTICO - José Luis Rojas Aguilar (European Scientific Journal, ESJ, 2014)
This article seeks to model the new theories of multidimensional poverty measurement , the model proposed in this paper seeks to pave the problem of heterogeneity in the definition of poverty (Needs vs capabilities) analyzed extensively in the literature on this issue, to propose a stochastic model seeks to address the multidimensional approach requires the measurement of poverty and break the paradigms of measuring poverty indicators with static and deterministic , to provide a dynamic picture of the evolution of poverty and to understand that poverty is a process and not an end in itself and that it multiple factors which have a historical memory in their formation, this model is applied to the various dimensions of income poverty in Mexico discriminating between the population of the rural areas involved and urban .